The Lepers Live in the Mountain: The “refuge” for lepers in Anápolis, Goiás, Brazil (1930-1970) - Giovana Galvão Tavares; Josana de Castro Peixoto; Dulcinea Maria Barbosa Campos; Janes Socorro da Luz; Rogério Seabra Monteiro (Fronteiras: Journal of Social, Technological and Environmental Science, 2015)
Keeping the necessary restrictions of a research in progress, this article aims to present the formation and consolidation of the ‘refuge’ for lepers in Anápolis. For research purposes the following steps were preformed: collection and analysis of oral reports, photographic images and documents of individual archives and institutions, public and private. The leprosarium instituted in Anápolis was not part of a similar existing chain of colonies in Brazil; the leprosarium was built during the 1930s by the Sociedade São Vicente de Paulo (São Vicente de Paulo Society) with the help of public and private donations, posteriorly, in the 1940s, it was deactivated leading to the creation of the Colônia Santa Marta (Santa Marta Colony) in Goiânia. During the 1950s the refuge resurfaced and began to aggregate the sickly fugitives of the colonies and, during the following decades, the survivors lived off of donations (food, clothing, etc.) made by the local society, of which were delivered at the Mountain to avoid the sick from coming into the city. Due to this fact, groups of individuals in situations of poverty who lived in Anápolis joined the lepers and constituted a sickly and poverty stricken territory, abandoned by public power, at the mercy of groups that at many times were responsible for existing local conflicts. Keywords: Territory; Leprosy; Refuge; Place